An ethnopharmacological survey of herbal medicines use among pregnant and postpartum women in Souss Massa (Morocco) - Bouqoufi, Afaf; Lahlou, Laila; Ait El Hadj, Fatima; Boujraf, Said; Abdessadek, Mohammed; Khabbal, Youssef (Frontiers in Pharmacology, 2025)
IntroductionPregnant women use medicinal plants for the treatment of illnesses associated with pregnancy. Women might resort to using medicinal plants because they are easily accessible and inexpensive. This study aims to determine the prevalence, to document and to analyse the traditional use of medicinal plants during pregnancy.MethodsA cross-sectional study was conducted among pregnant and postpartum women attending the Obstetrics and Gynecology Service at the regional hospital center, Hassan II of Souss Massa region. An Ethnopharmacological survey was used for data collection. After collection, data were coded, entered, and analyzed by Jamovi Software.ResultsA total of 420 women participated in this study. The mean age was 28.7 ± 6.35. The prevalence of herbal medicine consumption among pregnant and postpartum women is 48% with CI 95% (43.2%–52.7%). 35 varieties of medicinal plants from 22 families were used during pregnancy. Each of the other families had one species. Plant extracts were primarily prepared through decoction, infusion, maceration, Fumigation, extraction, and powder. The oral route was the most common route of administration used, about the number of plates used by pregnant and postpartum women (90.9%).ConclusionThe utilization of herbal medicine among pregnant mothers in this study was high in the region of Souss Massa. This research expands our understanding of the role that different plant species have in the management of disorders that affect women during pregnancy.